Optical tomography: Velocity profile measurement using orthogonal and rectilinear arrangements - Ruzairi, Abdul Rahim; Yusri, Mohd Yunosa; Mohd Hafiz Fazalul, Rahiman; Siti Zarina, Mohd Muji; Chiam, Kok Thiam; Herlina, Abdul Rahim (Elsevier Ltd., 2012)
Link to publisher's homepage at http://www.elsevier.com/